2016
DOI: 10.1002/cncr.30132
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients with delirium in the emergency department: A frequent and distressing problem that calls for better assessment

Abstract: PrecisDelirium is acknowledged as a common complication of cancer that frequently results in a visit to the emergency department, yet it is poorly assessed and the diagnosis missed as a consequence. Given that age is a major risk factor for delirium, and as population demographics change, there is a critical need to develop optimal delirium screening strategies for cancer patients who access this point of care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, MDAS is not validated in the ED setting, and it is significantly longer than the CAM. Further research is needed to compare the two tools in the ED setting, probably in addition to evaluation of all patients with suspected delirium by a psychiatrist, as suggested by Lawlor . A short sensitive tool is needed to detect delirium in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…However, MDAS is not validated in the ED setting, and it is significantly longer than the CAM. Further research is needed to compare the two tools in the ED setting, probably in addition to evaluation of all patients with suspected delirium by a psychiatrist, as suggested by Lawlor . A short sensitive tool is needed to detect delirium in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the lower rate of delirium in the community may suggest that delirium prompts a crisis admission to hospital or inpatient hospice and that increasing care burdens and behavioral challenges make staying at home a less viable option for delirious patients and their caregivers. 74…”
Section: Main Findings Of the Studymentioning
confidence: 99%
“…21 The ideal delirium screening tool should have a high level of sensitivity, be validated against a diagnostic reference standard, and be brief and easy to use with minimal training. 10,22…”
Section: Introductionmentioning
confidence: 99%
“…21 The ideal delirium screening tool should have a high level of sensitivity, be validated against a diagnostic reference standard, and be brief and easy to use with minimal training. 10,22 Currently, the use of delirium screening tools in palliative care is varied and their utility is unclear. 1,23 A recent survey of UK and Irish palliative care physicians reported that 59% do not use a formal screening tool on patients admitted to inpatient palliative care units.…”
Section: Introductionmentioning
confidence: 99%